Leafy automata for higher-order concurrency - Dixon, A; Lazic, R; Murawski, AS; Walukiewicz, I (Springer, 2021)
Finitary Idealized Concurrent Algol ( 𝖥𝖨𝖢𝖠 ) is a prototypical programming language combining functional, imperative, and concurrent computation. There exists a fully abstract game model of 𝖥𝖨𝖢𝖠 , which in principle can be used to prove equivalence and safety of 𝖥𝖨𝖢𝖠 programs. Unfortunately, the problems are undecidable for the whole language, and only very rudimentary decidable sub-languages are known.